Comparison of HbA1c Levels in Normal-Weight and Obese Type 2 Diabetes Mellitus Patients at Dr. Pirngadi General Hospital, Medan, North Sumatra, Indonesia - Sagala, Daniela; Nainggolan, Ranatha NH; Sinurat, Suryati; Butar-Butar, Harry; Siahaan , Jekson Martiar (Indonesian Journal of Medicine, 2024)
Background: Diabetes mellitus is a collection of metabolic diseases caused by impaired insulin secretion, insulin action, or both so that it has the characteristics of hyperglycemia. Increased will cause a decrease in glucose delivery to the plasma membrane, resulting in insulin resistance in muscle and adipose tissue. This study aimed to compare HbA1c in normal weight and obese individuals with type 2 DM at Dr. Pirngadi hospital.Subjects and Method: This was a cross-sectional study was conducted at Dr. Pirngadi Hospital, Medan, North Sumatera, Indonesia, on May 2022. A sample of 50 patients diagnosed with Type 2 Diabetes Mellitus (T2DM, HbA1c ≥6.5%). The study variables were HbA1c and body mass index (BMI). Independent t-test was used to compare HbA1c levels between normal weight and obese participants.Results: HbA1c in type 2 DM patients with obesity (Mean= 11.49; SD= 0.60) is higher than those with normal weight (Mean= 8.71; SD= 0.34), with p= 0.002.Conclusion: HbA1c in type 2 DM patients with obesity is higher than those with normal weight.